Effects of the percentage of skeletal muscle and body fat on physiological changes after a judo match - Takashina, T.; Kushi, H.; Yoshida, A.; Fukada, K.; Onuma, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Competitive Judo is divided into 7 classes according to weight, with men divided into the following classes: <60 kg, 66 kg, 73 kg, 81 kg, 90 kg, 100 kg, and >100 kg. Body fat percentage increases with increasing weight class, with a particularly rapid increase in the >90 kg classes. The purpose of this study was to compare physiological changes before and after a Judo match between men <90 kg group and >90 kg group. Subjects and Methods: This study included 15 men with >10 years of Judo experience who were divided into 2 groups: one is"<90 kg (n = 7)"and ">90 kg(n = 8)". Body composition (body fat percentage, skeletal muscle percentage, and extracellular water)was measured before the match, while heart rate, blood lactate concentration, tympanic temperature, and skin temperature (thigh, Tsurite, and Hikite temperatures) were measured before and 1, 10, and 20 min after the match. Results: Body fat percentage was significantly higher in the >90 kg group (20.8 ± 2.3%) than in the <90kg group (11.6 ± 1.4%) (p<0.01). Skeletal muscle percentage was significantly higher in the <90kg group (50.1 ± 1.3%) than in the >90 kg group (43.7 ± 1.6%) (p<0.01), and extracellular water was significantly higher in the <90 kg group (0.20 ± 0.003l/kg) than in the >90 kg group (0.17 ± 0.007l/kg) (p<0.05). Blood lactate concentrations measured at 1, and 10 min after the match were 5.8 ± 0.9mmol/l and 3.3 ± 0.5mmol/l, respectively, in the <90 kg group and 9.5 ± 0.5mmol/l and 5.7 ± 0.7mmol/l, respectively, in the >90 kg group. These differences at both time points were significant (p<0.05). Thigh, Tsurite, and Hikite temperatures measured 10 min after the match were 34.3 ± 0.3 degrees Celsius (C), 34.4 ± 0.3 degrees C and 34.3 ± 0.2 degrees C, respectively, in the <90 kg group and 35.0 ± 0.1 degrees C, 35.1 ± 0.2 degrees C and 34.9 ± 0.2 degrees C, respectively, in the >90 kg group. These values were higher in the >90 kg group than in the <90 kg significantly (p<0.05). Conclusions: The present study revealed that Judo athletes with lower skeletal muscle and higher body fat percentages accumulated more blood lactate and experienced greater increases in skin temperature after the Judo match. Judo athletes with lower percentage of skeletal muscle may have fewer muscle capillaries compared to those in athletes with a higher percentage of muscle. Therefore, blood lactate accumulates owing to a lack of oxygen supply for the working muscles. Moreover, increased body fat may result in increased skin temperature because of inefficient heat diffusion from the skin. The results of this study demonstrate that body composition, specifically the percentage of skeletal muscle and body fat affects physiological changes after a Judo match.